Anterior Segment Dysgenesis in A Child, A Rare Case Report: What Should We Do? Poster Presentation - Case Report - Resident - Permatasari, Devi Sarah Intan; Hermawan, Dicky; Loebis, Rozalina (Majalah Oftalmologi Indonesia, 2023)
Introduction : Anterior segment dysgenesis affects a various range of ocular structure, including: cornea, iris, ciliary body, anterior chamber, and lens associated with approximate 50% of glaucoma Case Illustration : A 20 month-old boy presented with bilateral corneal opacity. VA was 6/480 on both eye. Examination revealed bilateral central corneal opacity with keratolenticular adhesions, anterior lens dislocation and opacification, aniridia, and posterior segment were difficult to evaluate. The IOP were 17.3 mmHg and 14.6 mmHg in the right and left eye respectively. The aforementioned feature contributed to the diagnosis of Type II Peters Anomaly (PA). Lens aspiration combined with adhesiolysis on the LE was performed. Patient was given topical antibiotic, corticosteroid, and anti- glaucoma medication post-operatively. Postoperative course showed no complication and the corneal opacity diminished Discussion : Lens aspiration in combination with adhesiolysis was performed because the presence of cataract interfered the visual axis and increased the risk of corneal decompensation due to keratolenticular adhesions. We considered to perform the surgery on the LE first because the corneal opacity was milder than the RE. Glaucoma is an almost ineluctable issue and medical therapy are necessary. Further evaluation was required to determine if a similar procedure is needed for the fellow eye and whether the IOL implantation was going to enhance the visual prognosis in the future Conclusion : The keratolenticular adhesions and corneal opacity in type II PA make the surgical approach more challenging. Cautious manipulation can prevent further corneal decompensation. In addition, parents should receive extensive counseling regarding the complications and prognosis